2021
DOI: 10.3389/fnins.2021.686740
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Relationship Between Subjective Symptoms of Visual Fatigue and Visual Functions

Abstract: PurposeTo investigate whether the severity of symptoms of visual fatigue might be associated with clinical visual measures and basic visual functions, such as accommodation, vergence, and contrast sensitivity.MethodsIn this study, 104 students were recruited (25 males, 79 females, Age 23.4 ± 2.5) for this study. Those with high myopia, strabismus, anisometropia, eye disease or history of ophthalmological surgery were excluded. The included subjects completed a questionnaire that assesses the severity of visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 48 publications
1
18
1
Order By: Relevance
“…This is in line with previous research which demonstrated low spatial‐contrast sensitivity in dry eyes 48 . In parallel, recent findings have suggested that visual fatigue is associated with changes in clinical visual measures and basic visual functions, including contrast sensitivity 49 . Conversely, in the present study, photopic and mesopic visual acuity was unchanged in both groups.…”
Section: Discussionsupporting
confidence: 93%
“…This is in line with previous research which demonstrated low spatial‐contrast sensitivity in dry eyes 48 . In parallel, recent findings have suggested that visual fatigue is associated with changes in clinical visual measures and basic visual functions, including contrast sensitivity 49 . Conversely, in the present study, photopic and mesopic visual acuity was unchanged in both groups.…”
Section: Discussionsupporting
confidence: 93%
“…We believe that this finding is clinically important regardless of the underlying cause. Several studies have indicated a strong relationship between VF disorder and vision‐related symptoms as well the developmental‐perceptual status 39–41 . It is recommended that more studies be performed in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated a strong relationship between VF disorder and vision-related symptoms as well the developmentalperceptual status. [39][40][41] It is recommended that more studies be performed in this area. In addition, evaluating the effect of optometric vision therapy on the VF in diabetics requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Stereoscopic visual fatigue (SVF) is an important problem hindering the development of stereoscopic display applications, especially virtual reality (VR) display applications for deep immersion. SVF, which can be manifested as blurred vision, diplopia and other binocular anomalies symptoms, is a state of weakness, easy fatigue, and unsustainable vision of a visual-related organ that occurs after viewing the stereoscopic content due to excessive load [ 1 , 2 , 3 , 4 ]. The long-term exposure to electronics-induced visual fatigue is associated with a variety of serious visual health problems, such as decreased retinal vision, optic neurasthenia, dry eyes, cataracts, and glaucoma [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%